2011
DOI: 10.1038/eye.2011.48
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of horizontal macular contraction after surgical removal of epiretinal membranes

Abstract: Purpose To determine whether horizontal macular contraction caused by epiretinal membranes (ERMs) improves after surgical removal. Methods In this prospective, single-center, observational study, 63 consecutive patients with unilateral idiopathic ERM in one eye and no retinal disease in the fellow eye underwent pars plana vitrectomy. Fundus photography and optical coherence tomography (OCT) were performed preoperatively and at 3 months postoperatively. The area enclosed by superior and inferior major vessels f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
(34 reference statements)
3
21
0
Order By: Relevance
“…4,31 In the present study, we hypothesized that contraction of the ERM may affect the ONH and peripapillary RNFL beyond the macula. 4,31 In the present study, we hypothesized that contraction of the ERM may affect the ONH and peripapillary RNFL beyond the macula.…”
Section: Discussionmentioning
confidence: 93%
“…4,31 In the present study, we hypothesized that contraction of the ERM may affect the ONH and peripapillary RNFL beyond the macula. 4,31 In the present study, we hypothesized that contraction of the ERM may affect the ONH and peripapillary RNFL beyond the macula.…”
Section: Discussionmentioning
confidence: 93%
“…The retinal changes induced by tangential traction may appear on the fundus examination as follows: irregular wrinkling, nerve fiber layer dragging, ectopic fovea, winding corkscrew vessels surrounding the overlying ERM, or major vessel straightening and crowding [ 99 ]. Fundus photography and, in particular, red-free or blue-reflectance imaging, can highlight the presence of ERM [ 17 ].…”
Section: Epiretinal Membranementioning
confidence: 99%
“…Vitreomacular surgery releases these tractional forces, by eliminating points of attachment between the membrane and the retina and leading to visual improvement over several months [7][8][9]. On OCT, lowering of CMT is observed, but a return to a completely normal contour with its characteristic foveal depression is seldom realized [8,10].Pre-operative predictive signs of post-operative vision improvement remain difficult to establish.…”
Section: Introductionmentioning
confidence: 99%
“…Vitreomacular surgery releases these tractional forces, by eliminating points of attachment between the membrane and the retina and leading to visual improvement over several months [7][8][9]. On OCT, lowering of CMT is observed, but a return to a completely normal contour with its characteristic foveal depression is seldom realized [8,10].Pre-operative predictive signs of post-operative vision improvement remain difficult to establish. OCT characteristics in patients with ERM have been extensively studied but these have not been found so far to be predictive of visual outcome [11].Based on autofluorescence images before and after vitreoretinal surgery, Nitta et al suggested that if pre-operative hyperfluorescent lines present in a number of ERM eyes disappeared postoperatively, a better visual outcome was possible [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation